The state of melanoma: challenges and opportunities. (17th April 2016) - Merlino, Glenn; Herlyn, Meenhard; Fisher, David E.; Bastian, Boris C.; Flaherty, Keith T.; Davies, Michael A.; Wargo, Jennifer A.; Curiel‐Lewandrowski, Clara; Weber, Michael J.; Leachman, Sancy A.; Soengas, Maria S.; McMahon, Martin; et al.
Summary: The Melanoma Research Foundation (MRF) has charted a comprehensive assessment of the current state of melanoma research and care. Intensive discussions among members of the MRF Scientific Advisory Council and Breakthrough Consortium, a group that included clinicians and scientists, focused on four thematic areas – diagnosis/early detection, prevention, tumor cell dormancy (including metastasis), and therapy (response and resistance). These discussions extended over the course of 2015 and culminated at the Society of Melanoma Research 2015 International Congress in November. Each of the four groups has outlined their thoughts as per the current status, challenges, and opportunities in the four respective areas. The current state and immediate and long‐term needs of the melanoma field, from basic research to clinical management, are presented in the following report.